Effect of CYP2D6, CYP3A5, and MDR1 genetic polymorphisms on the pharmacokinetics of risperidone and its active moiety - Xiang, Qian; Zhao, Xia; Zhou, Ying; Duan, Jing Li; Cui, Yi Min (Journal of clinical pharmacology, 2010)
Clinical studies suggest that plasma levels of risperidone and its active moiety (risperidone + 9-hydroxyrisperidone) correlate with adverse drug effects. The aim of this study is to evaluate the pharmacogenetic variability in the disposition of risperidone and the active moiety in healthy Chinese subjects. A 2-mg single dose of risperidone is orally administered to 23 healthy Chinese subjects. The risperidone and 9-hydroxyrisperidone serum concentrations are measured. The polymorphic alleles of CYP2D6*10, CYP3A5*3, MDR1 C1236T, G2677T/A, and C3435T are determined in each subject. The mean maximum plasma concentration and area under the time-concentration curve extrapolated to infinity for risperidone are significantly higher in subjects possessing the CYP2D6*10 allele than in those with the CYP2D6*1/*1 and *1/*10 genotype. For active moiety, the subjects who carry both homozygous CYP2D6*10 and homozygous CYP3A5*3 have 98% higher area under the time-concentration curve extrapolated to infinity and 59% higher maximum plasma concentration compared with other CYP2D6 EM subjects. The MDR1 2677GA genotype may also play a role in risperidone pharmacokinetics. Further studies are needed to explore the impact of MDR1 2677GA and CYP3A5 polymorphisms on risperidone therapy.